2018
DOI: 10.1016/j.jinf.2018.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Candida periprosthetic joint infection: A rare and difficult-to-treat infection

Abstract: CPJI is usually a chronic disease in patients with comorbidities and risk factors for Candida infection. Treatment success is low, and prosthesis removal improves outcome. Although there is insufficient evidence that use of antifungals with antibiofilm activity has additional benefits, our experience indicates it may be recommendable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Our data suggest that there are two factors significantly associated with an increased odds of fungal PJIs when compared with bacterial PJIs; antimicrobial therapy within three months before the diagnosis of PJI was associated with a 3.4-fold increased odds of having a fungal PJI, and presence of wound drainage lasting longer than five days prior to the diagnosis of PJI was associated with a 7.3-fold increased odds of fungal PJI. In our study, consistent with what has been reported in the literature, the most commonly identified fungus was Candida albicans, which was recovered in twenty-five (60.9%) cases followed by Candida parapsilosis (24.4%) [13,30] (Table 2). It has been reported that Candida albicans makes large and complex biofilms compared to other candida species [13,17], thus contributing to its pathogenicity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data suggest that there are two factors significantly associated with an increased odds of fungal PJIs when compared with bacterial PJIs; antimicrobial therapy within three months before the diagnosis of PJI was associated with a 3.4-fold increased odds of having a fungal PJI, and presence of wound drainage lasting longer than five days prior to the diagnosis of PJI was associated with a 7.3-fold increased odds of fungal PJI. In our study, consistent with what has been reported in the literature, the most commonly identified fungus was Candida albicans, which was recovered in twenty-five (60.9%) cases followed by Candida parapsilosis (24.4%) [13,30] (Table 2). It has been reported that Candida albicans makes large and complex biofilms compared to other candida species [13,17], thus contributing to its pathogenicity.…”
Section: Discussionsupporting
confidence: 91%
“…Both centers acquired and collected data in a similar way and both centers used the same software. As explained by L. Escola-Verge et al, searching and treating for candida intertrigo could be a reasonable measure to avoid candida PJI [30]. We were not able to record how many patients had cutaneous candidiasis as that can be a potential risk factor.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…often grow in a biofilm formation adhering to the medical device 25 . Aggravating, candida PJI predominantly effects older patients with various comorbid conditions and perioperative risk factors that limits treatment management 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the adherent bacteria begin to produce an extracellular mucus matter consisting exopolysaccharides. Bacteria, living in biofilms are widely metabolism inactive, making antibiotics/antimycotics less effective 26 , 33 35 .…”
Section: Discussionmentioning
confidence: 99%